Predictors of Ramadan fasting during pregnancy. Issue 4 (December 2016) - van Bilsen, Lily A.; Savitri, Ary I.; Amelia, Dwirani; Baharuddin, Mohammad; Grobbee, Diederick E.; Uiterwaal, Cuno S.P.M.
Abstract: Although the health effects of Ramadan fasting during pregnancy are still unclear, it is important to identify the predictors and motivational factors involved in women's decision to observe the fast. We investigated these factors in a cross sectional study of 187 pregnant Muslim women who attended antenatal care visits in the Budi Kemuliaan Hospital, Jakarta, Indonesia. The odds of adherence to fasting were reduced by 4% for every week increase in gestational age during Ramadan [odds ratio (OR) 0.96; 95% confidence interval (CI) 0.92, 1.00; p  = 0.06] and increased by 10% for every one unit increase of women's prepregnancy body mass index (BMI) (OR 1.10; 95% CI 0.99, 1.23; p  = 0.08). Nonparticipation was associated with opposition from husbands (OR 0.34; 95% CI 0.14, 0.82; p  = 0.02) and with women's fear of possible adverse effects of fasting on their own or the baby's health (OR 0.47; 95% CI 0.22, 1.01; p  = 0.05 and OR 0.43; 95% CI 0.21, 0.89; p  = 0.02, respectively), although they were attenuated in multivariable analysis. Neither age, income, education, employment, parity, experience of morning sickness, nor fasting during pregnancy outside of Ramadan determined fasting during pregnancy. Linear regression analysis within women who fasted showed that the number of days fasted were inversely associated with women's gestational age, fear of possible adverse effects of fasting on their own or the fetal health, and with opposition from husbands. In conclusion, earlier gestational age during Ramadan, husband's opinion and possibly higher prepregnancy BMI, influence women's adherence to Ramadan fasting during pregnancy. Fear of adverse health effects of Ramadan fasting is common in both fasting and non-fasting pregnant women.